PENGARUH KOMPENSASI, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN PRODUKSI PT. HOLI MINA JAYA SLUKE KABUPATEN REMBANG - Muthohar, Muhammad Iqbal; Nurhidayati, Anik (STIE Wiyatamandala, 2023)
The purpose of this research is to demonstrate how salary, motivation, and leadership style affect production staff' job satisfaction at PT. Holi Mina Jaya Sluke, Rembang Regency. The 98 workers that made up the manufacturing division of PT. Holi Mina Jaya Sluke in Rembang Regency were the population utilized in this research. ways for gathering data via a questionnaire. A saturated sample is used in the sampling procedure. techniques for multiple linear regression data analysis. The findings revealed that 1) compensation (X1) had a significant positive impact on employee job satisfaction with tcount > ttable (5.247 > 1.6612); 2) motivation (X2) has a significant positive impact on employee job satisfaction with tcount > ttable (4.347 > 1.6612); and 3) leadership style (X3) has no significant negative impact on employee job satisfaction with tcount (-0.674 1.6612). According to the adjusted R2 value of 0.621, differences in remuneration, motivation, and leadership style may account for 62.1% of the variance in work satisfaction among employees in the manufacturing division of PT. Holi Mina Jaya Sluke, Rembang Regency. While 37.9% of the explanation comes from factors outside the model.